Problems of Religious Life: Agnostics in Students - Christopher Howard Wonohadidjojo; Kevin Anandita Rukmana; Priscillia Imanuela; Rayhan Sudiro; Yusuf Muhammad Yasin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2002)
The heroes of Indonesian independence  fighters have tried hard to seize the rights of our nation's independence in order to get freedom from the invaders and gain recognition from the eyes of the world that Indonesia is an independent and sovereign nation. Indonesia became independent on August 17, 1945 and Indonesia established Pancasila as the state ideology including red and white flag as the state symbol. However, Indonesia needs a national identity and a language that is used for national communication as a sovereign, independent nation. As a result, Indonesian was chosen as the state's identity and as the unifying language on August 18, 1945. The Indonesian nation's identity, Indonesian, plays a significant part in demonstrating Indonesia's presence to the rest of the globe. Indonesian was created prior to independence, despite being declared the state language on August 18, 1945. Specifically, during the second youth congress, which took place on October 28, 1928, and which is also known as the Youth Pledge. Many things in the current globalization era are affected by the passing of time and the effects of globalization. One of them is the threat to the existence of Indonesian, the language that unites us. We communicate in a variety of foreign languages on a regular basis, and many people also combine these languages with Indonesian. As a result, we must preserve the Indonesian language and contribute to its existence. The younger generation should effectively protect the Indonesian language in the age of globalization, as stated in the youth oath.